Correlação da destreza manual com taxa de complicação em cirurgia de catarata por facoemulsificação durante o período de residência em Oftalmologia - Vieira, Ibraim Viana [UNIFESP] (2021)
Objective: To evaluate total and specific surgical complication rate in phacoemulsification throughout ophthalmology residency program and relate these rates to manual dexterity measured at the beginning of the residency program with an ophthalmology surgery simulator that uses virtual reality. Methods: Prospective cohort study involving 14 newly enrolled residents in the ophthalmology program at Escola Paulista de Medicina and Universidade Estadual Paulista – Botucatu campus. Residents underwent manual dexterity assessment with a surgery simulator that uses virtual reality called Eyesi® (VRmagic, Mannheim, Germany). The rates of surgical complication in phacoemulsification were calculated during the second and third year of training. Complications were divided into: incision, anterior capsule, posterior capsule, intraocular lens and others. Differences between groups with and without complications were assessed using the MannWhitney test. Through logistic regression, we evaluated the relationship between rates of surgical complications with: manual dexterity score, age and gender of patients and anesthetic and surgical techniques employed. Results: The manual dexterity score was 266.96 ± 80.59 (mean ± standard deviation) arbitrary units (UA). Throughout the study, 1227 surgeries were performed, with complications occurring in 251 (20.46%) of these. Procedures that presented complications related to the anterior capsule (p = 0.0005), posterior capsule (p = 0.0022) and intraocular lens (p = 0.0037) were associated with lower scores of dexterity when compared to uncomplicated procedures. Each unit of improvement in the initial score represented a 0.37% decrease in the chance of complication occurrence. Surgeries performed with anesthetic block or general anesthesia presented 1.75 times the chance of complication in relation to surgeries with topical anesthesia.Conclusion: Manual dexterity score assessed in the pre-training period was related to lower rates of intraoperative complications during the phacoemulsification learning period. The Eyesi® simulator could be used in the selection of candidates for residency in ophthalmology, and surgical fellowship, or in stratifying residents as to the chance of complication, allowing the development of individualized teaching programs. Both strategies could reduce training costs and provide less risk to patients.